Self-Concept, Self-Efficacy, and Critical Thinking Skills among Islamic Senior High School Students in Indonesia - Nurteti, Lilis (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2025)
This study examines the relationship between self-concept, self-efficacy, and critical thinking skills among Islamic senior high school students in Indonesia. Using a quantitative survey design, the study involved 64 students of Madrasah Aliyah Negeri 1 Darussalam, Ciamis, Indonesia. Data were collected through questionnaires measuring self-concept and self-efficacy, while students’ critical thinking skills were measured using a test instrument. The data were analyzed through correlational statistics to determine the relationship between each independent variable and critical thinking skills, as well as their simultaneous relationship. The findings show that self-concept has a positive correlation with critical thinking skills, with a correlation coefficient of 0.681. Self-efficacy also shows a positive correlation with critical thinking skills, with a coefficient of 0.574. When analyzed simultaneously, self-concept and self-efficacy have a stronger relationship with critical thinking skills, indicated by a multiple correlation coefficient of 0.736. These findings suggest that students’ critical thinking skills are not merely shaped by cognitive instruction, but also by how students perceive themselves and how strongly they believe in their academic capacity. The study highlights the importance of integrating psychological support, active learning, Islamic values, and reflective pedagogy in Islamic senior high school education.